THE EFFECT OF SCHOOL PRINCIPAL ACADEMIC SUPERVISION AND TEACHER SELF-DEVELOPMENT ON THE TEACHERS’ PROFESSIONAL COMPETENCE AT PUBLIC ELEMENTARY SCHOOLS IN NORTH RUPAT BENGKALIS - Dumaria; Gimin; Sumarno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
School Principal's academic supervision and teacher self-development are the main priorities in efforts to improve teachers’ professional competence. The research is aimed to determine the effect of academic supervision (X1) and teacher self-development (X2) on the professional competence of teachers (Y) at SDN in North Rupat. The research uses quantitative research. The research is descriptive research with a total sample of 88 people. Simultaneously, there is the effect of the School Principal’s Academic Supervision (X1) and Teacher Self-Development (X2) on Teacher Professional Competence (Y) at SDN in North Rupat. It can be proven by tcount > ttable X1 with 1.735 > 1.662. For X2 12.643 > 1.662, a significance level (sig.) of 0.012 and 0.167, which are higher than 0.05, hence H0 is rejected and H1 is accepted. Thus, the percentage influence between the two independent variables influences the Teachers’ Professional Competence as a variable at 80.4%, and the others at 19.6% are influenced by other variables or factors that cannot be mentioned in this research.